2021
DOI: 10.5194/gmd-14-2635-2021
|View full text |Cite
|
Sign up to set email alerts
|

Developing a common, flexible and efficient framework for weakly coupled ensemble data assimilation based on C-Coupler2.0

Abstract: Abstract. Data assimilation (DA) provides initial states of model runs by combining observational information and models. Ensemble-based DA methods that depend on the ensemble run of a model have been widely used. In response to the development of seamless prediction based on coupled models or even Earth system models, coupled DA is now in the mainstream of DA development. In this paper, we focus on the technical challenges in developing a coupled ensemble DA system, especially how to conveniently achieve effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Sun et al (2021) confirmed the effectiveness of the module-integration framework, as the DA framework DAFCC1 employs the module-integration framework for integrating the codes of DA methods and for online data exchange between the model and DA methods. To further evaluate the effectiveness, we use the Community Earth System Model (CESM;Hurrell et al, 2013) version 1.2.1 (called the baseline version) as well as the air-sea flux algorithm used in the model.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Sun et al (2021) confirmed the effectiveness of the module-integration framework, as the DA framework DAFCC1 employs the module-integration framework for integrating the codes of DA methods and for online data exchange between the model and DA methods. To further evaluate the effectiveness, we use the Community Earth System Model (CESM;Hurrell et al, 2013) version 1.2.1 (called the baseline version) as well as the air-sea flux algorithm used in the model.…”
mentioning
confidence: 59%
“…This framework can automatically and efficiently handle argument passing between a model and a module, even when they use different data structures, grids, or parallel decompositions. 4) C-Coupler3.0 includes a common framework (Sun et al, 2021) for conveniently developing a weakly coupled ensemble data assimilation (DA) system. This framework provides online data exchanges between a model ensemble and a DA method, for better parallel performance.…”
mentioning
confidence: 99%
“…C-Coupler2, the 2.0 version of C-Coupler developed at Tsinghua University, has following outstanding advantages: 1) the flexible coupling configuration interfaces, including coupling frequencies and model grids; 2) automatic coupling processing like data interpolation; 3) dynamic three-dimensional coupling capability; 4) promote model nesting and incremental operation; 5) capability of adaptive restart capability. C-Coupler2 has been applied in a few coupled models and coupled ensemble data assimilation [2] [15].…”
Section: The Coupler Component Modelmentioning
confidence: 99%